Lean Management model to improve production efficiency in an MYPE in the textile sector - Candelario-Cordova, Vannia (2023)
In Peru, the textile sector represents 6.3% of GDP within the manufacturing sector, being one of the most important in the country. Peru is considered one of the main exporters of organic pima cotton, however, the main problem in the textile sector is low efficiency, with the national average being 50.3%, remaining below the average of other countries such as Colombia (79.12%) India (90%) and Bangladesh (41% to 62%). The causes that generate low efficiency are: disorder in the work area, absence of standardized processes and erroneous preventive maintenance plan. The present study proposes a lean model based on the 5S components, Standardized Work and the autonomous pillar of the TPM, these tools have the objective of reducing the causes presented that cause low efficiency. The present proposed research manages to reduce rework from 13.39% to 7.39%, reaches a 5S authorship level of over 75% and increases production efficiency from 44.78% to 50.3%; With this, a precedent is set that contributes to the increase in the efficiency of the country's textile SMEs.